Mouse skeletal muscle adaptations to different durations of treadmill exercise after the cessation of FOLFOX chemotherapy - Halle, Jessica L.; Counts, Brittany R.; Zhang, Quan; James, Kylie M.; Puppa, Melissa J.; Alway, Stephen E.; Carson, James A. (Frontiers in Physiology, 2023)
FOLFOX (5-fluorouracil, leucovorin, oxaliplatin) chemotherapy is a treatment for colorectal cancer that can induce persistent fatigue and metabolic dysfunction. Regular exercise after chemotherapy cessation is widely recommended for cancer patients and has been shown to improve fatigue resistance in mice. However, gaps remain in understanding whether the early systemic and skeletal muscle adaptations to regular exercise are altered by prior FOLFOX chemotherapy treatment. Furthermore, the effects of exercise duration on early metabolic and skeletal muscle transcriptional adaptations are not fully established. Purpose: Investigate the effects of prior FOLFOX chemotherapy treatment on the early adaptations to repeated short- or long-duration treadmill exercise, including the fasting regulation of circulating metabolic regulators, skeletal muscle COXIV activity and myokine/exerkine gene expression in male mice. Methods: Male C57BL6/J mice completed 4 cycles of FOLFOX or PBS and were allowed to recover for 4-wks. Subsets of mice performed 14 sessions (6d/wk, 18m/min, 5% grade) of short- (10min/d) or long-duration (55min/d) treadmill exercise. Blood plasma and muscle tissues were collected 48-72 hours after the last exercise bout for biochemical analyses. Results: Long-duration exercise increased fasting plasma osteocalcin, LIF, and IL-6 in healthy PBS mice, and these changes were ablated by prior FOLFOX treatment. Slow-oxidative soleus muscle COXIV activity increased in response to long-duration exercise in PBS mice, which was blocked by prior FOLFOX treatment. Fast-glycolytic plantaris muscle COXIV activity increased with short-duration exercise independent of FOLFOX administration. There was a main effect for long-duration exercise to increase fasting muscle IL-6 and COXIV mRNA expression independent of FOLFOX. FOLFOX administration reduced muscle IL-6, LIF, and BDNF mRNA expression irrespective of long-duration exercise. Interestingly, short-duration exercise suppressed the FOLXOX induction of muscle myostatin mRNA expression. Conclusion: FOLFOX attenuated early exercise adaptations related to fasting circulating osteocalcin, LIF, and IL-6. However, prior FOLFOX treatment did not alter the exercise adaptations of plantaris muscle COXIV activity and plasma adiponectin. An improved understanding of mechanisms underlying exercise adaptations after chemotherapy will provide the basis for successfully treating fatigue and metabolic dysfunction in cancer survivors.